History of international broadcasting. - Wood, James 1920- (Institution of Engineering and Technology, 2000)
The book reviews developments in the following fields: international broadcasting; short-wave (SW) sales; foreign policy; broadcast transmitter industry; antenna arrays; and tube manufacturing industry.